The larva and pupa of Culicoides bambusicola Lutz observed with SEM, and additional notes on the adult (Diptera Ceratopogonidae) - Ronderos, Maria Marcela (2000)
The larva and pupa of Culicoides bambusicola are redescribed and illustrated, including photomicrographies, based on the examination with both Scanning Electron Microscopy (SEM) and phase-contrast stereoscope. The larva exhibits the characters stated by previous authors for larvae of tree hole breeding species. A diagnosis and illustrations of the adult stage from type material and specimens emerged in laboratory is also provided. The specimens were collected breeding in tacuara canes internodes in northeastern Argentina.